PROPOSING AN INNOVATIVE BUSINESS MENTORING FRAMEWORK FOR INDONESIAN EARLY-STAGE STARTUP : CASE STUDY AT FOUNDERPLUS - Senjaya, Andreas
The number of people who want to establish a startup in Indonesia is increasing, but the high risk of startup failure needs to be managed effectively. One way to increase the chances of success and sustainability of an early stage startup is to provide business mentoring. There are many entities, such as business incubators, that offer business mentoring services as part of their programs, but their effectiveness still needs improvement. The primary objective of this research is to identify and analyze the crucial factors that contribute to the success of business mentoring. Through this study, the author aim to determine which factors play a more significant role than others and propose a more comprehensive and effective business mentoring framework. The factors that influence the effectiveness of business mentoring will be analyzed by conducting literature studies and in-depth interviews with several expert sources. The ranking of these factors will be carried out using the Analytic Hierarchy Process (AHP) tool. Having an understanding of the critical factors that influence the effectiveness of business mentoring is crucial in proposing a business mentoring framework that concentrates on the areas that have the most significant impact on the output of business mentoring. This research can be useful for startup industry players, especially business incubator organizers, in improving their business mentoring programs. The research can also help early stage startup founders in Indonesia to receive a quality and impactful business mentoring process. Future research can focus on exploring interventions that can be carried out to increase the effectiveness of business mentoring. The ultimate goal is to increase the chances of success for early stage startups to become mature companies.